P PENGARUH PEMBERIAN PIJATAN PADA TUNGKAI KAKI TERHADAP PENURUNAN SKALA KELELAHAN PADA PASIEN GAGAL JANTUNG DI RUMAH SAKIT X - Julianto Julianto; Yuniarti Yuniarti; Mariana Mariana (Journal of Nursing Invention, 2021)
Heart failure is where the heart as a pump that is incapable of meeting the blood requirement for tissue metabolism is due to an increase in age. Heart failure sufferers experience fatigue. Pharmacological and non-pharmacological therapy with complementarytherapies such as leg massage. This study aims to determine the influence of leg massage to decrease the allergic scale in heart failure patients. An expression method that uses a one-group pre-post design approach or draft test. The number of research samples is 20 patients fatigue in heart failure that is experiencing fatigue. The results of this research before massage limbs obtained the value of 0,370, after massage limbs can be a significant value of 0,558. Results of the p-value (0.000) < α (0,05) have seen the decline of massage limbs in patients with heart failure.